Exploitation of Diagnostic Computed Tomography Scans to Assess the Impact of Nutrition Support on Body Composition Changes in Respiratory Failure Patients. (23rd August 2013) - Braunschweig, Carol A.; Sheean, Patricia M.; Peterson, Sarah J.; Gomez Perez, Sandra; Freels, Sally; Troy, Karen L.; Ajanaku, Folabomi C.; Patel, Ankur; Sclamberg, Joy S.; Wang, Zebin
Abstract : Background : Assessment of nutritional status in intensive care unit (ICU) patients is limited. Computed tomography (CT) scans that include the first to fifth lumbar region completed for diagnostic purposes measures fat and lean body mass (LBM) depots and are frequently done in ICU populations and can be used to quantify fat and LBM depots. The purpose of this study was to assess if these scans could measure change in skeletal muscle (SKT), visceral adipose (VAT), and intermuscular adipose (IMAT) tissue and to examine the association between the amount of energy and protein received and changes in these depots. Methods : Cross‐sectional area of SKT, VAT, and IMAT from CT scans at the third lumbar region was quantified at 2 time points (CT1 and CT2). Change scores between CT1 and CT2 for each of these depots and the percentage of estimated energy/protein needs received were determined in 33 adults that with acute respiratory failure. Descriptive statistics and multiple regression was used to evaluate the influence of baseline characteristics and the percentage energy/protein needs received between CT1 and CT2 on percentage change/day between CT1 and CT2 on SKM, IMAT, and VAT. Results : Participants were on average (SD) 59.7 (16) years old, received 41% of energy and 57% of protein needs. The average time between CT1 and CT2 was 10 (5) days. SKM declined 0.49%/day (men P = .07, women P = .09) and percentage of energy needs received reduced loss (β = 0.024, P = .03). No change in VAT or IMAT occurred. Conclusions : CT scans can be exploited to assess change in body composition in ICU patients and may assist in detecting the causal link between nutritional support and outcomes in future clinical trials.